Steel gratings as an innovative temporary roads pavement - Artur Juszczyk; Adam Wysokowski (Budownictwo i Architektura, 2016)
The needs related to reduction of lead time and quality of construction determines implementation of the new technologies. An example of such an activity is a development of pavements used to build temporary roads, carried out mainly for the needs of equipment and materials delivery to a construction site. This is especially important in civil engineering, where location is dictated by a number of local conditions, which often is associated with the occurrence of adverse groundwater conditions. Commonly used traditional design solutions of temporary roads such as unpaved roads or roads made by concrete slabs require good ground conditions or proper stabilized subsoil, which may ultimately result in a significant increase of the cost of the construction. Modern temporary paving structures not only transmit the exploitation load on the subsoil. They use subsoil, as a an structure cooperating in load distribution, so it is possible to use such a construction of road on a low-bearing soil. An innovative solution in this case are three-dimensional steel grids cooperating with a subsoil. The paper describes the preliminary modeling studies of this type of pavement structures.